Effects of Non-Tariff Measures on Agricultural Export Performance in COMESA - Stein Masunda; Gabriel Mhonyera; Daniel Francois Meyer (The Thinker)
Both classical and neo-classical economists have long held the convention that free trade is a significant generator of welfare of nations. Despite, the exploitation and discriminatory application of Non-Tariff Measures (NTMs) as some form of Non-Tariff Barriers (NTBs), which are an alternative to tariffs, has substantially expanded and is persistently constraining the path towards absolute free trade. This growing incidence has invoked the recognition of the compelling need to enhance the transparency of existing NTMs and promote research on their impact in developing countries as well as within and outside regional groupings such as COMESA. This study employs the gravity model to study the effects of Sanitary and Phytosanitary (SPS) and Technical Barriers to Trade (TBT) measures on intra-COMESA exports. The findings indicate that NTMs have diverse effects on exports within the COMESA region. On one end, SPS measures are export enhancing whilst TBT measures negatively affect intra-COMESA agricultural export volumes. Given the results of this research, COMESA members are encouraged to reduce the application of TBT measures in order to stimulate exports within the bloc, and to expand the application of SPS measures so as to promote the trade in agricultural products.